2021
DOI: 10.1016/j.ebiom.2021.103583
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning features from diffusion tensor imaging improve glioma stratification and identify risk groups with distinct molecular pathway activities

Abstract: Background To develop and validate a deep learning signature (DLS) from diffusion tensor imaging (DTI) for predicting overall survival in patients with infiltrative gliomas, and to investigate the biological pathways underlying the developed DLS. Methods The DLS was developed based on a deep learning cohort (n = 688). The key pathways underlying the DLS were identified on a radiogenomics cohort with paired DTI and RNA-seq data (n=78), where the prognostic value of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…DWI techniques allow for the analysis of water mobility and tissue microstructure [35,36]. It can also be used to analyze the microstructure of brain tumors supporting differential diagnosis and grading [37][38][39] and to help evaluate therapy effects [40,41]. ADC values can vary within a single DMG between enhancing and non-enhancing tumor areas, maybe more frequently in cases with ATRX loss [33].…”
Section: Discussionmentioning
confidence: 99%
“…DWI techniques allow for the analysis of water mobility and tissue microstructure [35,36]. It can also be used to analyze the microstructure of brain tumors supporting differential diagnosis and grading [37][38][39] and to help evaluate therapy effects [40,41]. ADC values can vary within a single DMG between enhancing and non-enhancing tumor areas, maybe more frequently in cases with ATRX loss [33].…”
Section: Discussionmentioning
confidence: 99%
“…The Kaplan-Meier method was then applied to explore the prognostic significance of the AI score. Based on the gene expression profile, the potential biological pathways underlying WSI cluster and AI cluster were identified [ 29 ]. First, differentially expressed genes (DEGs) between every subgroup stratified by the WSI cluster were identified using DESeq2 R package.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, numerous studies have reported that gliomas have specific molecular parameters, such as IDH-mutation ( Chen et al, 2017 ; Kesler et al, 2019 ) and MGMT promoter methylation ( Chen et al, 2017 ). To date, deep neural networks have been utilized to extract dMRI metrics like ADC and FA value, and to assist IDH, MGMT, and other molecule subtype classification and prognosis prediction of glioma patients ( Aliotta et al, 2019 ; Z. Huang et al, 2021 ; Yan et al, 2021 ).…”
Section: Structural Connectome and The Alternations In Gliomasmentioning
confidence: 99%